2010
DOI: 10.2319/061109-333.1
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory Performance and Chewing Cycle Kinematics—Are They Related?

Abstract: Objective: To compare chewing cycle kinematics of subjects with better and poorer masticatory performance. Materials and Methods: A cross-sectional study compared masticatory performance, based on the breakdown of the artificial test food CuttersilH, in 30 subjects with Class I occlusion. Individuals with median particle sizes greater and lesser than the median value for the entire sample were categorized as poorer (15) and better (15) performers, respectively. While chewing Cuttersil, threedimensional jaw mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 29 publications
7
38
0
2
Order By: Relevance
“…The closing path was also associated to quality of mastication, being the closing angle negatively correlated with food mixing ability (5) and a convex closing path related to better masticatory function (6). Similar results were reported by Lepley et al (7), who found a more horizontal path of cycle closure among better masticatory performers rather than in poorer chewers. Yamashita et al (3) stated that the chewing cycle apparently increases its lateral component when increased masticatory efficiency is required, as during the mastication of large bolus or hard food.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The closing path was also associated to quality of mastication, being the closing angle negatively correlated with food mixing ability (5) and a convex closing path related to better masticatory function (6). Similar results were reported by Lepley et al (7), who found a more horizontal path of cycle closure among better masticatory performers rather than in poorer chewers. Yamashita et al (3) stated that the chewing cycle apparently increases its lateral component when increased masticatory efficiency is required, as during the mastication of large bolus or hard food.…”
Section: Introductionsupporting
confidence: 76%
“…function. Previous studies have used different materials, with distinct characteristics, number of particles, size and weight, for analysis, such as wine gum, almond, paraffin, wax cube, gummy jelly (4)(5)(6)(7)(8), while the present study used cubes made of a rubber based artificial material. It has been reported that chewing cycle alters its pattern according to the hardness or the size of bolus (3) and to the rheological properties of the food (15), suggesting the reason for such divergence of data.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Liedberg et al (2004) showed higher food comminution in patients with fixed dental prostheses than in RDP wearers. Because masticatory impairment can adversely affect quality of life (Lepley et al, 2010), the effects of different prostheses on mastication are important to determine.…”
Section: Introductionmentioning
confidence: 99%
“…Isto é um aspeto favorável, pois a melhoria na movimentação mandibular pode contribuir para a eficiência na trituração e, associada à mobilidade da língua, para a limpeza da cavidade oral, 39 lateralização e organização do bolo alimentar. 40 Os nossos resultados podem ser explicados pelo facto de a mastigação ser uma função complexa e individual, influenciada pela morfologia e condições de saúde das estruturas orofaciais, oclusão dentária, 19,20 articulação temporomandibular, salivação, área de contacto oclusal, sensibilidade intraoral, capacidade funcional muscular e postura cervical [41][42][43] que modificam de acordo com o desenvolvimento do indivíduo. 44,45 Além disso, o outro estudo 46 refere uma mudança no comportamento muscular durante a DM que retorna ao nível observado inicialmente, antes do término da intervenção ortodôntica, ou seja, o recurso da disjunção maxilar não é capaz de promover modificações na musculatura e mantê-las.…”
Section: Discussionunclassified
“…Alteração no tipo mastigatório, preferência por um dos lado da cavidade oral para a trituração dos alimentos; 17,18 modificação na forma, duração e frequência dos ciclos mastigatórios, resultante da diminuição da força muscular e da modificação na área de contacto oclusal 19-21 e ineficiência mastigatória. 11,19 A DM pode amenizar a respiração oral e a atresia maxilar. 22 Por isto esta pesquisa objetivou analisar a influência desta terapêutica na mastigação, comparando resultados pré-disjunção maxilar (pré-DM) e pós-disjunção maxilar (pós-DM).…”
Section: Introductionunclassified